COVID-19 AND PERIODONTAL DISEASE - ETHIOPATHOGENIC AND CLINICAL IMPLICATIONS - Maria-Alexandra Martu; George-Alexandru Maftei; Irina-Georgeta Sufaru; Igor Jelihovschi; Ionut Luchian; Loredana Hurjui; Ioana Martu; Liliana Pasarin (Romanian Society of Oral Rehabilitation, 2020)
SARS-CoV-2 was first discovered in December 2019 as the etiologic agent of a serious respiratory illness later called COVID-19 or coronavirus disease 2019. The first COVID-19 case was reported in Wuhan, China and since then, has reached a pandemic level, spreading all over the world and multiplying faster than any other respiratory disease known until now in modern times, with more than 85 million confirmed cases and almost 2 million deaths, according to the latest information from the World Health Organization (WHO). Periodontal disease is one of the most common diseases of the oral cavity that has systemic implications in the overall health homeostasis. It is an inflammatory disease that involves a series of dysbiotic events caused by periodontopathogenic microflora that causes destruction of the periodontal tissues locally, and an exacerbated proinflammatory status systemically. Diabetes mellitus, metabolic syndrome and obesity, hypertension, cardiovascular disease, chronic kidney disease, chronic obstructive pulmonary disease and autoimmune diseases have been identified as risk factors for both periodontitis and severe Covid-19 infections. These diseases have similar inflammatory pathways that are involved in the progression of these conditions, thus, it is fair to assume a pathological common link.